If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3w + 36 = 4w + -18 Reorder the terms: 36 + 3w = 4w + -18 Reorder the terms: 36 + 3w = -18 + 4w Solving 36 + 3w = -18 + 4w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-4w' to each side of the equation. 36 + 3w + -4w = -18 + 4w + -4w Combine like terms: 3w + -4w = -1w 36 + -1w = -18 + 4w + -4w Combine like terms: 4w + -4w = 0 36 + -1w = -18 + 0 36 + -1w = -18 Add '-36' to each side of the equation. 36 + -36 + -1w = -18 + -36 Combine like terms: 36 + -36 = 0 0 + -1w = -18 + -36 -1w = -18 + -36 Combine like terms: -18 + -36 = -54 -1w = -54 Divide each side by '-1'. w = 54 Simplifying w = 54
| 3(k+7)=75 | | x^5+2x^2=0 | | 5a+2(3a+4)-2a= | | 2b^2-3b=5 | | N=55000-2000x | | 7v-5=4v+4 | | 3(v+4)+v=20 | | 5x-5+6-3x=0 | | q*4q*5q= | | 5(2y+10)=110 | | 3x+2y-z=23 | | 3-5x=4+2x | | X^4-3x^2-x^3+4x-4=0 | | x=6.25+0.25y+-0.5z | | 5(x+6)+2=37 | | 3(x+1)-x+4=2x+8 | | 282-10x=20x+12 | | z^3-i*z^2+4z-4i=0 | | x^4-7x^3+7x^2+42x+63=0 | | 4(x+12)+2(x+18)=-6 | | x^4+11x^3+7x^2+42x+63=0 | | x^4+6x^3+7x^2+42x+63=0 | | (5-x)*(6x+2)+5=0 | | 2*x^2+4=0 | | 4(x+2)-3(x+1)=3 | | (5-x)*(6x+2)=5 | | x^4+6x^3-7x^2-42x-63=0 | | 2(3x-1)-4(2x+5)=-5 | | 7x-5=2b+15 | | 3x+2y-z=28 | | 3(4k-11)=75 | | 4*(12-6y)+2y=-7 |